Microsporidia-nematode associations in methane seeps reveal basal fungal parasitism in the deep sea - Sapir, Amir; Dillman, Adler R.; Connon, Stephanie A.; Grupe, Benjamin M.; Ingels, Jeroen; Mundo-Ocampo, Manuel; Levin, Lisa A.; Baldwin, James G.; Orphan, Victoria J.; Sternberg, Paul W. (Frontiers in Microbiology, 2014)
The deep sea is Earth's largest habitat but little is known about the nature of deep-sea parasitism. In contrast to a few characterized cases of bacterial and protistan parasites, the existence and biological significance of deep-sea parasitic fungi is yet to be understood. Here we report the discovery of a fungus-related parasitic microsporidium, Nematocenator marisprofundi n. gen. n. sp. that infects benthic nematodes at methane seeps on the Pacific Ocean floor. This infection is species-specific and has been temporally and spatially stable over 2 years of sampling, indicating an ecologically consistent host-parasite interaction. A high distribution of spores in the reproductive tracts of infected males and females and their absence from host nematodes' intestines suggests a sexual transmission strategy in contrast to the fecal-oral transmission of most microsporidia. N. marisprofundi targets the host's body wall muscles causing cell lysis, and in severe infection even muscle filament degradation. Phylogenetic analyses placed N. marisprofundi in a novel and basal clade not closely related to any described microsporidia clade, suggesting either that microsporidia-nematode parasitism occurred early in microsporidia evolution or that host specialization occurred late in an ancient deep-sea microsporidian lineage. Our findings reveal that methane seeps support complex ecosystems involving interkingdom interactions between bacteria, nematodes, and parasitic fungi and that microsporidia parasitism exists also in the deep-sea biosphere.